Assumptions of the Project of the New Core Curriculum for the Subject of Health Education: An Analysis of the Discourse Among Supporters and Opponents on Internet Portals - Zaworska-Nikoniuk, Dorota (Przegląd badań edukacyjnych, 2025)
The attempt to introduce a new subject of health education to Polish schools in 2024 sparked demonstrations and social protests. The main problem addressed in this paper was: What categories of analysis and meanings given to the new core curriculum for health education may be identified in the articles published online? Data was collected by searching internet archives using the Google search engine; thus, 32 articles posted on internet portals were selected for research using discourse analysis. A proprietary constructed categorization key was used in the analysis, which was employed to map the thematic distribution in a selection of scientific articles devoted to online discourse. Five framework categories were distinguished, namely inspirational figures and authorities, descriptions of the contents of the subject, the reasons for introducing it, potential consequences, and the meanings attributed by the opponents and supporters of the reform. The origin and political entanglement of the demonstrations were highlighted, conclusions were drawn, and recommendations for pedagogy involved in social change were formulated. Próba wprowadzenia nowego przedmiotu edukacja zdrowotna do polskich szkół w 2024 roku, wywołała demonstracje i protesty społeczne. Problem główny brzmiał następująco: Jakie kategorie analizy i znaczenia nadawane nowej podstawie programowej do edukacji zdrowotnej wyróżnić można w przekazie artykułów zamieszczanych na portalach Internetowych? Metodą zbierania danych było  przeszukiwanie archiwów internetowych przy pomocy wyszukiwarki google do badań wyłoniłam 32 artykuły zamieszczone na portalach internetowych; zaś metodę analizy danych stanowiła analiza dyskursu. W prowadzonej analizie wykorzystałam własny skonstruowany klucz kategoryzacyjny, który posłużył do odczytywania rozkładu tematycznego zbioru artykułów naukowych poświęconych internetowemu dyskursowi. Wyodrębniłam pięć kategorii ramowych tj. osoby inspirujące i autorytety, określenia treści przedmiotu, przyczyny wprowadzenia, potencjalne konsekwencje, wraz ze znaczeniami nadawanymi im przez przeciwników i zwolenników reformy. Wskazałam na rodowód i polityczne uwikłanie demonstracji, wyprowadzając z badań wnioski i rekomendacje dla pedagogiki zaangażowanej w zmianę społeczną.